STUDI KASUS POLA PEMBERIAN REMUNERASI RESIDEN DI RSUD DR. MOEWARDI SURAKARTA - Sudirman; Laksono Trisnantoro; Andreasta Meliala (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2016)
Background: Since the commencement of the national health insurance program (JKN), patient visits to hospitals have increased. The same is true for patient referrals with specialist cases. The limited ability of specialist doctors in dealing with the increasing number of specialized cases has made hospitals start considering resident personnel to help provide medical services, especially in teaching hospitals. The magnitude of the resident's role in providing medical services in teaching hospitals needs serious attention, especially in relation to the resident's right to receive remuneration for medical services carried out in accordance with the mandate of Law Number 20 of 2013 concerning medical education. Objectives: This study aimed to evaluate the policy of providing remuneration or incentives for residents who provide medical services at Dr. Moewardi Surakarta. Methods: This study is a non-experimental study with a descriptive case study design with a single holistic case design. The research was conducted at Dr. Moewardi and FK UNS during January–February 2016 with 10 respondents as research subjects and carried out by purposive sampling method. Results: Remuneration for residents that has been applied in Dr. Moewardi was very dependent on the university-based system applied by FK UNS in organizing specialist medical education programs. Resident remuneration that has been given only includes incentives and does not refer to Law Number 20 of 2013 concerning medical education which regulates resident incentives. The provision of resident incentives has the same pattern regardless of the type of specialization and level of competence. Conclusions: The pattern of incentives that have been implemented by RSUD Dr. Moewardi does not difffferentiate incentives based on the type of specialization or level of competence and is not in accordance with Law Number 20 of 2013 concerning medical education.